Resolution of Posterior Nutcracker Syndrome through Left Renal Vein Ligation: A Case Report - Tadayon, Niki; Allameh, Farzad (Archives of Men’s Health, 2023)
This case report presents the clinical course of a 54-year-old male patient diagnosed with posterior Nutcracker Syndrome (NCS). The patient experienced recurrent episodes of macroscopic hematuria and severe left flank pain. He was diagnosed with retro-aortic left renal vein (RLRV), an unusual congenital abnormality, which can result in the compression of the left renal vein between the aorta and the vertebra. Initial attempts at conservative management and endovascular interventions were unsuccessful. An open surgical intervention was ultimately performed. The surgery involved ligation of the left renal vein. Postoperatively, the patient experienced marked improvement in symptoms, with complete resolution of hematuria and pain. Furthermore, renal function remained stable, and no kidney-related complications were reported. This case suggests that, in certain situations where endovascular intervention and transposition of LRV or re-implantation of the left gonadal vein are not feasible, ligation of the LRV may provide a safe and practical treatment option for patients with posterior NCS. Future research is needed to validate these findings.